Neuropilins, as Relevant Oncology Target: Their Role in the Tumoral Microenvironment - Dumond, Aurore; Pagès, Gilles (Frontiers in Cell and Developmental Biology, 2020)
Angiogenesis is one of the key mechanisms involved in tumor growth and metastatic dissemination. The Vascular Endothelial Growth Factor (VEGF) and its receptors (VEGFR) represent one of the major signaling pathways which mediates angiogenesis. The VEGF/VEGFR axis was intensively targeted by monoclonal antibodies or by tyrosine kinase inhibitors to destroy the tumor vascular network. By inhibiting oxygen and nutrient supply, this strategy was supposed to cure cancers. However, despite a lengthening of the progression free survival in several types of tumors including colon, lung, breast, kidney and ovarian cancers, modest improvements in overall survival were reported. Anti-angiogenic therapies targeting VEGF/VEGFR are still used in colon and ovarian cancer and remain reference treatments for renal cell carcinoma. Although the concept of inhibiting angiogenesis remains relevant, new targets need to be discovered to improve the therapeutic index of anti-VEGF/VEGFR. Neuropilin 1 and 2 (NRP1/2), initially described as neuronal receptors, stimulate angiogenesis, lymphangiogenesis and immune tolerance. Moreover, overexpression of NRPs in several tumors is synonymous of patients’ shorter survival. This article aims to overview the different roles of NRPs in cells constituting the tumor microenvironment to highlight the therapeutic relevance of their targeting.